Contribution of Larvae Developing on Corn and Dry Beans to the Adult Population of Western Bean Cutworm in Michigan. Issue 1 (18th November 2020) - Bunn, Dakota C; Dias de Oliveira, Eduardo; Springborn, Frederick; Gonzalez-Meler, Miquel A; Miller, Nicholas
Abstract: The western bean cutworm, Striacosta albicosta (Smith) (Lepidoptera: Noctuidae), is historically a pest of both corn ( Zea mays L. (Poales: Poaceae)) and dry beans ( Phaseolus sp. L. (Fabales: Fabaceae)) in the western Great Plains. However, it has recently undergone an eastward range expansion establishing itself across the Corn Belt in 25 states and 4 Canadian provinces. To mitigate the effects of infestation in Michigan, foliar insecticides are used in dry beans, whereas management of the pest in corn relies more heavily on the use of Bt-expressing hybrids. In this study stable carbon isotope analysis was used to determine what crop adult moths developed on as larvae with analysis showing that very few of the adult moths developed on dry beans. These results suggest that beans and corn are not suitable as co-refuges and that mainly adults which developed on corn are contributing to the next generation of western bean cutworm in Michigan.